2020
DOI: 10.1159/000505365
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl Ester Transfer Protein Inhibitors and Cardiovascular Outcomes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Cholesteryl ester transfer protein (CETP) inhibitors increase serum high-density lipoprotein cholesterol (HDL-c) concentration; however, their impact on cardiovascular outcomes is not clear. This systematic review examines the effect of CETP inhibitors on serum lipid profiles, cardiovascular events, and all-cause mortality. Methods: We searched MEDLINE, Embase, and the Cochrane Library of Clinical Trials for placebo-controlled randomized controlled trials (RCTs) that examined the effect of a CETP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…CETP-inhibitors have mainly been investigated in other indications such as the treatment of hypercholesterolemia. A recent meta-analysis revealed that CETP inhibitors may reduce nonfatal myocardial infections or cardiovascular death, but the results did not reach statistical significance and the clinical relevance of these reductions is modest ( Taheri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…CETP-inhibitors have mainly been investigated in other indications such as the treatment of hypercholesterolemia. A recent meta-analysis revealed that CETP inhibitors may reduce nonfatal myocardial infections or cardiovascular death, but the results did not reach statistical significance and the clinical relevance of these reductions is modest ( Taheri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…CETP allows the transfer and exchange of neutral lipids such as CE (cholesteryl ester) and TG (triacylglycerol) between plasma and lipoproteins. It is proven to play important role in atherosclerosis [79]. Tomoda et al reported that chaetoviridin B (37) showed CETP (cholesteryl ester transfer protein) inhibitory activity with an IC 50 < 6.3 µM, whereas chaetoviridin A (31) had moderate inhibitory activity (IC 50 31.6 µM) [80].…”
Section: Cholesteryl Ester Transfer Protein Inhibitory Activitymentioning
confidence: 99%
“…A recent meta-analysis of 11 randomized controlled trials [51] examined the effects of CETP inhibitors on major cardiovascular events (MACE) and all-cause mortality, showing a non-significant reduction in the risk of non-fatal myocardial infarction (−7%) and death from cardiovascular causes (−8%).…”
Section: Increasing Cholesterol In Hdl: Pharmacological Trialsmentioning
confidence: 99%